Rekayasa Aplikasi Pengarsipan Surat Permohonan Hak Milik Tanah Dengan menggunakan Metode Prototyping - Rosi Subhiyakto, Egia; Parti Astuti, Yani; Wahyu Utomo, Danang (P3M Politeknik Negeri Cilacap, 2022)
National Land Agency received requests for land rights every day. The letters can be submitted through two stages of acceptance and archiving. Still using conventional systems makes data retrieval requires relatively more time. This research aims to design and build an information system data archiving for incoming request at the National Land Agency. The software has been designed with login feature, data management land owners and land owner data search and print feature data. Analysis of system requirements using object-oriented method which uses the use-case diagram in order to illustrate the functionality of the system and some of the criteria of non-functional requirements are also outlined. The next step was the coding implementation and evaluation of the system built. The system development method used was the prototyping method. The selection of this method was intended, therefore the client can get a clear picture of the system being built. Evaluation was conducted in the developer and the user environment. The evaluation in the user environment was done by distributing questionnaires covering three parameters namely the usefulness of the application, ease of use and user satisfaction. The results showed that the information systems built have a useful value (85.7%) and are easy to use (100%), therefore it satisfied the users.